Receding horizon based collision avoidance for UAM aircraft at intersections - Negasa Yahi; Jose Matute; Ali Karimoddini (Green Energy and Intelligent Transportation)
Urban Air Mobility (UAM) is an emerging aviation sector which the goal is to transform air transportation with safe, on-demand air travel for both passengers and cargo. UAM flight planning strategically separates flows of aircraft on intersecting routes vertically by allocating distinct flight levels to them, and aircraft are required to maintain the flight level when crossing the intersection. However, there is a possibility that an aircraft may fail to maintain the assigned flight level, leading to a potential conflict at intersections. This paper aims to address conflicts at intersections in the context of UAM, focusing on decentralized conflict detection and resolution. A novel approach is developed to facilitate information exchange among UAM components, including the provider of services to UAM, UAM operators, and the pilot in command. A receding horizon trajectory planning approach is proposed for the execution of conflict resolution, optimizing trajectory planning by eliminating potential problems and challenges associated with geometric approaches. The proposed trajectory planner considers the model and constraints of UAM aircraft, offering optimal solutions for safe separation at UAM airspace intersections. The significance of the proposed planning framework is demonstrated through simulations considering conflict at intersections by communicating the UAM components through request and replay services and generating resolution maneuvers on-the-fly for each aircraft involved in the conflict.